Comparing the linguistic complexity in receptive and productive modes - Jessie S. Barrot, (Penerbit UKM, 2015)
Several studies have investigated linguistic complexity as an index of proficiency and across genres. However, very little research has been conducted in determining the difference between the linguistic complexity during receptive and productive modes. This study, therefore, attempts to fill in such a gap by providing evidence on whether the linguistic complexity that pupils can process during receptive mode is higher than what they can utilize during productive mode. Specifically, this study sought to determine the linguistic complexity level of learners‘ written narratives (i.e. productive mode) and reading passages most comprehensible to them (MCRPs) (i.e. receptive mode) and whether all linguistic complexity indices in MCRPs are higher than the linguistic complexity indices in written narratives. To address these objectives, this study used a narrative film to elicit the written narratives from the participants via story reconstruction. Eight graded narrative reading passages were also used to determine the most comprehensible reading passage via multiple-choice test. Using a microstructure analysis tool, the findings suggest that while the overall receptive linguistic complexity of Grades 2, 4, and 6 pupils is higher than their productive linguistic complexity, interestingly, not all indices of linguistic complexity are higher during productive mode. The implications of these findings for classroom teaching are considered more particularly in the selection of reading materials and the aspect of linguistic complexity that needs to be adjusted to facilitate comprehension. This paper, then, concludes with some research directions that would shed light on the receptive-productive dimensions of linguistic complexity.